Faktor-Faktor yang Mempengaruhi Akuntabilitas Kinerja Pegawai Pemerintahan pada Badan Pengelolaan Keuangan Aset Daerah (BPKAD) Kota Pekanbaru (Jurnal Kendali Akuntansi, 2025)
The importance of employee performance accountability in transparent and efficient public financial management, particularly amid the demands for improved public service quality. This study aims to identify and analyze the factors affecting employee performance accountability, namely the regional government accounting system, accounting control, legislation, human resource quality, and reporting systems. The research employs a quantitative methodology with a descriptive approach. A census technique was utilized, where all employees of BPKAD, totaling 51 individuals, were designated as respondents. The data analysis technique employed is multiple regression to determine the influence of each independent variable on the dependent variable, which is employee performance accountability. The findings of the study indicate that the regional government accounting system, accounting control, and human resource quality significantly influence employee performance accountability. Conversely, legislation did not show a significant influence, while the reporting system approached the significance threshold. In conclusion, this study emphasizes that improving the quality of the accounting system, internal control, and human resource development is crucial for enhancing employee performance accountability at BPKAD Pekanbaru City. The implications of this research are expected to provide insights for decision-making and improvements in public financial management practices.